Water absorption and curing time performance of urea formaldehyde resin mixed with different amount phosphorous-based fire retardants. - Kamal, Izran; Ashaari, Zaidon; Abdul Malek, Abdul Rashid; Abood, Faizah; Saad, Mohamad Jani; Misran, Suffian; Rusli, Rafeadah; Thirmizir, Mohd Zharif (Universiti Malaysia Sabah, 2008)
The curing time and the properties of urea formaldehyde (UF) resin mixed with fire retardants, BP (mixture of boric acid, guanylurea phosphate and phosphoric acid), monoammonium phosphate (MAP) and diammonium phosphate (DAP) were studied. There were two amounts used, 8% w/w and 10% w/w. The curing time of the mixed resin was determined by using thermo oil at the temperature of 170ºC. Water absorption test and physical observations were done to evaluate the properties of the fire retardant-mixed resin. The non-fire retardant UF resin samples were used as controls. The solubility of MAP and DAP in the water at different weights also has been studied. The solubility test was done with and without the involvement of heat. The study showed that UF resin mixed with MAP and BP cured faster than DAP-mixed UF and control samples. The time taken for UF resin to mix with 10 % w/w and 8 % w/w MAP were 20 s and 28 s respectively. The time taken for UF resin mixed with 10 % and 8 % w/w DAP was slightly than the controls, which are 160 s and 150 s respectively. The time taken for UF resin mixed with 10 % w/w and 8 % w/w BP was 101 s and 92 s respectively.The curing time for control samples was 140 s respectively. MAP and DAP were shown to be highly soluble, as they took less than 1 minute to be dissolved in the water without heat, but BP took 30 minutes to be dissolved in the water without heat and less than 1 minute with heat. Water absorption test showed that the higher the amount of MAP, DAP and BP mixed into the resin, the higher would be the rate of water absorbed.